Security strategy : from requirements to reality - Stackpole, Bill.; Oksendahl, Eric. (Boca Raton, FL : CRC Press, 2011)
Addressing the diminished understanding of the value of security on the executive side and a lack of good business processes on the security side, Security Strategy: From Requirements to Reality explains how to select, develop, and deploy the security strategy best suited to your organization. It clarifies the purpose and place of strategy in an information security program and arms security managers and practitioners with a set of security tactics to support the implementation of strategic planning initiatives, goals, and objectives. --